E-cigarette vaping is associated with pro-fibrotic gene expression in kidney and liver tissues - Wanjun Gu; Howard Chang; Poorvi Saini; Samvel Gaboyan; Jarod Olay; Jorge A. Masso-Silva; John Shin; Ira Advani; Ashley Du; Cameron Brand; Joan Heller Brown; Alexia Perryman; et al. (Journal of Molecular Medicine, 2026)
Conventional tobacco use causes a wealth of diseases and adversely affects cells and organ systems across the body. The long-term effects of e-cigarette vaping on the same remain unclear. Identifying early pathogenic signals at the organ level via animal models may shed light on potential downstream effects in humans. Here we investigate transcriptomic changes in the kidney and liver, organs known to be damaged by long-term combustible tobacco use, of mice exposed daily to e-cigarette aerosols (vapor) with or without nicotine. C57BL/6 male 6–8 week-old mice underwent whole-body exposure to room air, e-cigarette (3rd generation box mod) vapor containing 70:30 propylene glycol and glycerin (PG: Gly) without nicotine (Vehicle), and e-cigarette vapor with 6 mg/mL freebase nicotine in 70:30 PG: Gly (E-cig) for 1 h daily for 3 months. RNA sequencing on kidney and liver tissues and apriori gene set analysis were performed. Unbiased principal component analysis identified closer clustering of E-cig and Vehicle groups, relative to Air, in the kidney. Assessment of the a priori gene set found nicotine to be associated with greater transcriptomic changes in the kidney while vehicle chemicals induced greater changes in the liver. Alterations in expression of Car3 and Foxo3 identify oxidative stress and inflammation in the renal system associated with e-cigarette exposure, while dysregulated Il6ra and Lpin1 in the liver highlight disruptions in lipid metabolism and immune signaling. Chronic inhalation of e-cigarette vapor alters gene expression in downstream organs, in a pattern most consistent with promotion of fibrosis and metabolic dysregulation, underscoring the need to define long-term pathophysiologic effects of e-cigarette vaping across the body.

A comprehensive review on wine authentication and traceability: Current issues, solutions and future perspectives - Hai-Qing Qiang; Hui-Wen Gu; Xiao-Li Yin; Zhan Meng; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2026)

Facile construction of a pH-responsive vaterite based abamectin delivery platform and visual tracking of micro-particle transport in cucumber plants - Chunhua Niu; Ge Bai; Wanjun Gu; Linxiang Zhou; Shengxue Liu; Zhong Wei; Kai Chen; Xuhong Guo (Chemical Engineering Journal, 2025)

Revealing the key antioxidant compounds and potential action mechanisms of Chinese Cabernet Sauvignon red wines by integrating UHPLC-QTOF-MS-based untargeted metabolomics, network pharmacology and molecular docking approaches - Zhi-Xin Peng; Hui-Wen Gu; Yuan Pan; Yan Wang; Jun Yan; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

A colorimetric sensor based on 4-MPBA Au@AgNPs for accurately identification of EnshiYulu tea grade - Yuting Guan; Siyu Wang; Guanghua Lei; Zikang Hu; Hengye Chen; Huiwen Gu; Xiaoli Yin; Yuanbin She; Wanjun Long; Haiyan Fu (Food Chemistry, 2024)

Discrimination and prediction of Qingzhuan tea storage year using quantitative chemical profile combined with multivariate analysis: Advantages of MRMHR based targeted quantification metabolomics - Zhi-Quan Li; Xiao-Li Yin; Hui-Wen Gu; Zhi-Xin Peng; Baomiao Ding; Zhenshun Li; Ying Chen; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Deep leaning in food safety and authenticity detection: An integrative review and future prospects - Yan Wang; Hui-Wen Gu; Xiao-Li Yin; Tao Geng; Wanjun Long; Haiyan Fu; Yuanbin She (Trends in Food Science & Technology, 2024)

Insight into the effect of cultivar and altitude on the identification of EnshiYulu tea grade in untargeted metabolomics analysis - Dan Zou; Xiao-Li Yin; Hui-Wen Gu; Zhi-Xin Peng; Baomiao Ding; Zhenshun Li; Xian-Chun Hu; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Transcriptomic Analysis of the Rat Dorsal Root Ganglion After Fracture - Xinyi Gu; Chen Huang; Shen Wang; Jin Deng; Shuhang Guo; Aihaiti Sulitan; Wanjun Gu; Qingguo Lu; Shaoxun Yuan; Xiaofeng Yin (Molecular Neurobiology, 2024)

UHPLC-QTOF-MS-based untargeted metabolomic authentication of Chinese red wines according to their grape varieties - Xiao-Li Yin; Zhi-Xin Peng; Yuan Pan; Yi Lv; Wanjun Long; Hui-Wen Gu; Haiyan Fu; Yuanbin She (Food Research International, 2024)

Revealing the chemical differences and their application in the storage year prediction of Qingzhuan tea by SWATH-MS based metabolomics analysis - Zhi-Quan Li; Xiao-Li Yin; Hui-Wen Gu; Dan Zou; Baomiao Ding; Zhenshun Li; Ying Chen; Wanjun Long; Haiyan Fu; Yuanbin She (Food Research International, 2023)

Experimental and artificial intelligence study on catalytic reforming of tar over bio-char surface coupled with hydrogen production - Shanhui Zhao; Yunliang Zhang; Wanjun Xu; Haiming Gu (Fuel, 2023)

UHPLC-QTOF-MS-based untargeted metabolomics and mineral element analysis insight into the geographical differences of Chrysanthemum morifolium Ramat cv. “Hangbaiju” from different origins - Wanjun Long; Xiuyun Bai; Siyu Wang; Hengye Chen; Xiao-Li Yin; Hui-Wen Gu; Jian Yang; Haiyan Fu (Food Research International, 2023)

Altered splenic miRNA expression profile in H1N1 swine influenza - Liangzong Huang; Jun Ma; Yankuo Sun; Yanli Lv; Wen Lin; Mingjie Liu; Changsong Tu; Pei Zhou; Wanjun Gu; Shuo Su; Guihong Zhang (Archives of Virology, 2015)

Mutagenesis analysis of porcine reproductive and respiratory syndrome virus nonstructural protein 7 - Minze Zhang; Zhenpeng Cao; Jiexiong Xie; Wanjun Zhu; Pei Zhou; Honglang Gu; Long Sun; Shuo Su; Guihong Zhang (Virus Genes, 2013)

Tracking miRNA precursor metabolic products and processing sites through completely analyzing high-throughput sequencing data - Li Guo; Hailing Li; Jiafeng Lu; Qi Yang; Qinyu Ge; Wanjun Gu; Yunfei Bai; Zuhong Lu (Molecular Biology Reports, 2012)

Xi River virus, a new bat reovirus isolated in southern China - Linfeng Du; Zongji Lu; Yu Fan; Keyin Meng; Yu Jiang; Yan Zhu; Shumin Wang; Wanjun Gu; Xiaohuan Zou; Changchun Tu (Archives of Virology, 2010)